2017
DOI: 10.1016/j.kint.2016.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathy associated with monoclonal gammopathy

Abstract: Thrombotic microangiopathy (TMA) is a rare disease comprising of a diverse set of disorders linked by a common histologic finding of endothelial injury. Monoclonal immunoglobulins may act as a potential trigger in the pathogenesis of TMA. To determine the prevalence of monoclonal gammopathy and clinicopathological features of TMA associated with monoclonal immunoglobulin, we performed a retrospective study in adults (18 and older) with a clinical diagnosis of TMA. Of 146 patients with TMA, we detected monoclon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 28 publications
1
66
0
2
Order By: Relevance
“…At the 2017 IKMG meeting in New Orleans, two additional subcategories were added to the non-organized and non-immunoglobulin categories of the classification scheme 35 . Thrombotic microangiopathy associated with monoclonal gammopathy was provisionally added as a subcategory of non-immunoglobulin deposits 42 , and a miscellaneous subcategory was added to the non-organized deposit category, which applies to pathological entities that are ultrastructurally similar to a non-monoclonal-immunoglobulin-related disease but are only sometimes associated with a monoclonal gammopathy. The MGRS-associated disorders included in this classification are discussed in more detail below.…”
Section: Updated Classification Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…At the 2017 IKMG meeting in New Orleans, two additional subcategories were added to the non-organized and non-immunoglobulin categories of the classification scheme 35 . Thrombotic microangiopathy associated with monoclonal gammopathy was provisionally added as a subcategory of non-immunoglobulin deposits 42 , and a miscellaneous subcategory was added to the non-organized deposit category, which applies to pathological entities that are ultrastructurally similar to a non-monoclonal-immunoglobulin-related disease but are only sometimes associated with a monoclonal gammopathy. The MGRS-associated disorders included in this classification are discussed in more detail below.…”
Section: Updated Classification Systemmentioning
confidence: 99%
“…Thrombotic microangiopathy is the endothelial injury seen most commonly in microangiopathy with haemolytic anaemia (MAHA). Thrombotic microangiopathy and MAHA can occur concurrently in patients with monoclonal gammopathies, including MM and WM 13,42,80,81 .…”
Section: Updated Classification Systemmentioning
confidence: 99%
“…A subset of patients with TMA have an associated MIg. 69 MIg can act as a potential trigger of TMA, producing atypical hemolytic uremic syndrome via dysregulation of the alternative pathway of complement, although precise mechanisms remain to be elucidated. 70 Similar to MIg-associated C3 glomerulopathy, it was recently shown that, among patients $50 years of age, the prevalence of monoclonal gammopathy in TMA was much higher than in the general population.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…1 Manifestations of TMA can be divided into peripheral which include thrombocytopenia and microangiopathic hemolytic anemia (MAHA), and renal including vascular thrombosis, mesangiolysis, endothelial swelling, and subendothelial accumulation of cellular material. 2 Malignancyassociated TMAs most commonly involved metastatic solid organ malignancies, usually with bone marrow infiltration. 3 There is a growing interest in the relationship between TMA and monoclonal gammopathies.…”
Section: Monoclonal Gammopathyassociated Thrombotic Microangiopathymentioning
confidence: 99%
“…In one study of 146 patients with TMA, monoclonal gammopathy was present in 13.7%. 2 MGUS was the most common diagnosis (n = 15), followed by POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes) syndrome (n = 2) and smoldering MM (n = 1), MM (n = 1), and 1 with a T-cell lymphocytic leukemia. It is important to note that some of these cases occur after infection, chemotherapy or hematopoietic stem cell transplantation in which the TMA cannot be directed attributed to the monoclonal gammopathy.…”
Section: Monoclonal Gammopathyassociated Thrombotic Microangiopathymentioning
confidence: 99%